The chief executives of Texas : from Stephen F. Austin to John B. Connally, Jr. - Hendrickson, Kenneth E. (Centennial series of the Association of Former Students, Texas A & M University, 1995)
"Texas govenors have often been portrayed as larger-than-life heroes, but most were not. In this thorough and colorful study of the leaders of the Lone Star State, Kenneth E Henderickson Jr., holds up a Texas sized magnifying glass to take a candid look at the lives and accomplishments of the now deceased forty two men and one woman who held the office of governor, or president of the Republic."